Granulation as a method for preparation of alkali halide salts for the growth of scintillation single crystals - Zaslavsky, B.G.; Vasetsky, S.I. (Functional Materials, 2004)
Described is a granulation method for high-purity alkali halide salts by spraying the melt into liquid nitrogen, as well as the design of the apparatus for realization of this process. Thermochemical treatment of the melt carried out directly in the apparatus allows to process the wastes of the manufacture of scintillation detectors (crystal cuttings and fragments or chips) for obtaining products suitable for repeated utilization as a starting material for crystal growth.